Art in Southeast Asia 1997 : Glimpses into the Future. - Hiroshima City Museum of Contemporary Art, Tokyo; The Japan Foundation; Isako, Kumagai; Junichi, Shioda; Navin Production Co. Ltd.; Osamu, Fukunaga; Shioda, Junichi; Supangkat, Jim; Tetsuro, Ishida; Yasuko, Furuichi; Yoshie, Okamoto (Tokyo : Museum of Contemporary Art, 1997)
Fajardo, Brenda V. ; Chandrasekaran ; Yu, Liew Kung ; Boonma, Montien ; Navin Production co, Ltd. (Navin Rawanchaikul) ; Suwage, Agus ; Puipia, Chatchai ; Eng Hwee Chu ; Cajipe-Endaya, Imelda ; Sanpitak, Pinaree ; Cheong, Wong Hoy ; Arahmaiani ; Christanto, Dadang ; Moelyono ; Alvarado, Nunelucio ; Sanggawa ; Siahaan, Semsar
2 ex. : 1 catalogus, 205 p. + 1 bijlage: Documentary Volume (ill.), 19 p.
biografie
Art in Southeast Asia 1997 : Glimpses into the Future, Museum of Contemporary Art, Tokyo, April 12 - June 1, 1997 ; Hiroshima City Museum of Contemporary Art, Tokyo, August 2 - September 15, 1997
English-Japanese
kunstcatalogus
Keywords: Azië